GASTROINTESTINAL PARASITES IN STREET DOGS IN ANIMAL SHELTER FROM THE BOGOTA D. C, COLOMBIA - Solarte-Paredes, Luz Dary (2013)
In order to determine the prevalence of Toxocara canis Werner, 1782, Ancylostoma caninum Ercolani, 1859 and Isospora canis Nemeseri, 1959 in street dogs at the Bogota Zoonosis Animal Shelter, seventy pooled fecal samples from cage floors were collected. Each pooled sample corresponded to one of 11 localities since the dogs were caged according to locality. Three serial samplings were performed. Each pooled sample was evaluated macroscopically and microscopically using qualitative and quantitative parasitological techniques to determine the presence of helminth eggs or oocysts. A total of 88,57% (n= 62) of the samples were parasite positive: 52,9% were positive for A. caninum; 7,1% for T. canis; 24,3% showed mixed infections of A. caninum and T. canis, 1,43% were positive for A. caninum, T. canis and I. canis and 2,9% were infected by A. caninum and I. canis. The pooled fecal samples from dogs from the localities of Usme, Bosa, Chapinero, Ciudad Bolívar and Kennedy in Bogota showed 100% infection prevalence, whereas the infection prevalence was between 70-80% in the pooled fecal samples from the rest of the localities. The sampled street dogs from the 11 localities showed single or mixed infections by several parasite species that have a zoonotic potential representing a public health risk to both humans and animals alike given the high parasite shedding into the environment.